1995
DOI: 10.1021/j100026a018
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Calculations of the Potential Surface for the Thermal Decomposition of the Phenoxyl Radical

Abstract: The thermal decomposition of the phenoxyl radical (1) to form CO plus C5H5' , a key reaction in the hightemperature oxidation of benzene, has been studied using ab initio quantum mechanical electronic structure methods. The complete active space (CAS) SCF method was used for geometry optimization of 10 stationary points on the ground-state potential energy reaction surface and computing their harmonic vibrational frequencies. Subsequent calculations using the multireference second-order perturbation theory bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
74
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 6 publications
10
74
0
Order By: Relevance
“…Subsequent reactions, which include as intermediates phenol (C 6 H 5 OH), phenoxy radicals (C 6 H 5 O), and a bicycle, result in the formation of the cyclopentadienyl radical (C 5 H 5 ). The overall reaction (R1), as a possible pathway to give the cyclopentadienyl radical, has also been confirmed in the works of Olivella et al (1995) and D'Anna (2005):…”
mentioning
confidence: 66%
“…Subsequent reactions, which include as intermediates phenol (C 6 H 5 OH), phenoxy radicals (C 6 H 5 O), and a bicycle, result in the formation of the cyclopentadienyl radical (C 5 H 5 ). The overall reaction (R1), as a possible pathway to give the cyclopentadienyl radical, has also been confirmed in the works of Olivella et al (1995) and D'Anna (2005):…”
mentioning
confidence: 66%
“…The mechanism for the CO elimination from phenoxy radical is already well established [4,8,9,32]. Ring contraction of the phenoxy radical (1) leads to the bicyclic intermediate (2), which upon C C bond fission converts to the 2,4-cyclopentadienyl formyl radical (3), which in turn dissociates to cyclopentadienyl (4) plus CO. An alternative pathway, which starts with C C bond fission in α position to the C O moiety in phenoxy, is higher in energy and not competitive [8].…”
Section: Pes and High-pressure Rate Expressionsmentioning
confidence: 99%
“…Thus, their recommended rate expression is k(T ) = 7.5E11 exp[−43.9 kcal mol −1 /(RT )] s −1 . The first theoretical studies on the thermal decomposition of phenoxy radicals are those by Olivella et al [8] in 1995 using the CASSCF and CASPT2 methods, and the G2(M) investigation by Liu et al [9] in 1996. Both studies support the mechanism for reaction (1) suggested by Colussi et al [4], which involves formation of a bicyclic intermediate that ring-opens to the 2,4-cyclopentadienyl carbonyl radical and subsequently eliminates CO to form cyclopentadienyl radical (cf.…”
Section: Introductionmentioning
confidence: 99%
“…7 We have previously investigated the mechanism for the formation of C 3 H 4 (propyne) from the CH 3 + C 2 H 2 reaction, the most likely precursor process of C 3 H 3 , 8 which can be produced readily by the abstraction reactions, X + C 3 H 4 → HX + C 3 H 3 , where X = H, OH, CH 3 , etc. The mechanism for the decomposition of the phenoxy radical producing CO + c-C 5 H 5 has been studied theoretically in detail, 9,10 whereas that for the decomposition of c-C 5 H 5 or its reverse process, C 3 H 3 + C 2 H 2 , is not well understood. This is the objective of the present investigation.…”
Section: Moskaleva and Linmentioning
confidence: 99%